Effects of transcranial direct current stimulation on neuro electrical activity in mice with migraine - Ji, Ziming; Zhang, Aobo; Wang, Jiahao; Chen, Tianyi; Wu, Jianliang (Frontiers in Neurology, 2025)
BackgroundAlthough transcranial direct current stimulation (tDCS) has demonstrated clinical efficacy in alleviating migraine symptoms, the neurophysiological mechanisms underlying its modulation of cortical excitability and restoration of neural homeostasis remain poorly elucidated.MethodsIn a nitroglycerin (NTG)-induced murine migraine model, low-intensity tDCS (0.25 mA, 20 min/day) was administered to experimental animals (NTG + tDCS, n = 6) with sham controls (CTRL + NS, n = 6). Multimodal evaluations included: (1) quantitative behavioral profiling via open-field test (OFT), assessing locomotor activity (total movement time, velocity), anxiety-like behaviors (grooming and head-scratching frequency), and rearing episodes; (2) chronic electrophysiological recordings of somatosensory cortex local field potentials (LFPs) before and after stimulation (0–60 min).ResultstDCS effectively normalized migraine-associated hyperlocomotion, with NTG + tDCS group exhibiting OFT parameters (movement time: 270.7 ± 41.6 s vs. 298.9 ± 29.6 s; velocity: 13.0 ± 0.3 mm/s vs. 7.4 ± 0.6 mm/s) comparable to CTRL + NS controls (p > 0.05). Electrophysiological analysis revealed triphasic neuromodulatory effects: (1) broadband entropy attenuation [1–200 Hz; F(3,68) = 14.2, p < 0.001]; (2) bidirectional reorganization of absolute spectral power, characterized by marked suppression of δ (1–4 Hz, −76 ± 14%, p < 0.001), low-γ (30–50 Hz, −83 ± 9%, p < 0.001), and high-γ (50–100 Hz, −68 ± 11%, p < 0.001) bands, alongside θ-band potentiation (4–12 Hz, +82 ± 32%, p < 0.01); (3) frequency-dependent redistribution of relative power, featuring θ (4–12 Hz, −52 ± 12%, q < 0.01), low-γ (30–50 Hz, −45 ± 17%, p < 0.001), and high-γ (50–100 Hz, −75 ± 6%, q < 0.001) reduction, contrasted with δ-band augmentation (1–4 Hz, +53 ± 38%, q < 0.001).ConclusionThese results establish that low-intensity tDCS ameliorates migraine pathophysiology through dual mechanisms: θ-band synchronization mediating behavioral normalization and γ-band desynchronization reducing neural noise. The δ/θ power reconfiguration implicates thalamocortical rhythm stabilization as a potential therapeutic target, advancing our mechanistic understanding of non-invasive neuromodulation in migraine management.